Susceptibilidad a deslizamientos a escala 1:5000, de la Zona Oeste de la Parroquia Selva Alegre, Cantón Saraguro, Provincia de Loja. - Villafuerte Encalada, Luis Santiago (2023)
The research work called "Susceptibility to landslides at a scale of 1:5000, of the West Zone of the Selva Alegre Parish, Saraguro Canton, Loja Province", has an area of 1505.46 ha. As a first step, information was collected in the office, to give way to the topographic survey, considering the road network, slopes, infrastructure, water network, and bodies of water, in order to develop the variables considered for the susceptibility map. For the cartographic construction, the quantitative method of the Analytical Hierarchy Process (AHP), postulated by Thomas Saaty in 1980, was used, which allowed the valuation, normalization and weighting of the applied factors. In the development of the susceptibility map, the ArcGIS 10.4 software was used, making the preparation of the variables (Geomorphology, Slope, Geology, Current Land Use), making use of the arcmap tools, for the correlation analysis and interpretation of the data obtained in the field, which allowed giving the corresponding valuation of weights to each variable and sub-variable, for the categorization of the final susceptibility map. Finally, the results of this project allowed the zoning of the areas susceptible to landslides represented in the final susceptibility map, developed under Datum WGS84-Zone 17 South, thus making it possible to highlight the zones before possible landslides. Key words: Susceptibility, Landslides, Saaty, Geology, Geomorphology, Land Use